Perswazyjna funkcja gestu ujmowania pod kolana w Iliadzie Homera - Chruściak, Ilona (Załącznik Kulturoznawczy, 2018)
The aim of this paper is to examine the gesture of clasping someone’s knees in act of supplication, which occurs several times in the Iliad. The singer applies this gesture, which must have been well known to the Homeric public, into the crucial and highly emotional scenes of the epic. The gesture of clasping someone’s knees originates from the battlefield and occurs in a variety of forms within the narrative. The paper traces the multiformity of the gesture and its evolution in oral poetry. It could be considered as a ritual gesture with a forceful persuasive power: one may state that the effective plea of the epic hero ought to incorporate the supplicant’s gesture.